Cognitive Training on the Solving of Mathematical Problems: An EEG Study in Young Men - Molina, Jahaziel (2021)
Objective. This study characterized the electroencephalographic correlation (rEEG) between prefrontal and parietal cortices in young men while solving logical-mathematical problems after 18 sessions of cognitive training. Method. Two training groups were formed: one trained with gradually increased complexity (CT), the other with no increase in complexity (ST). Results. CT had a greater number of correct responses in the post-training evaluation than ST and showed a higher correlation between the left frontopolar-parietal cortices in almost all EEG bands, and between the dorsolateral-parietal cortices in the alpha1 band while solving math problems post-training. Results suggest that major functional synchronization between the left prefrontal and parietal cortices plays an important role in improving mathematical problem-solving after cognitive training.